Synthesizing Seemingly Contradictory Seismic and Magnetotelluric Observations in the Southeastern United States to Image Physical Properties of the Lithosphere. (7th June 2019) - Murphy, Benjamin S.; Egbert, Gary D.
Abstract: Although seismic velocity and electrical conductivity are both sensitive to temperature, thermal lithosphere properties are derived almost exclusively from seismic data because conductivity is often too strongly affected by minor highly conductive phases to be a reliable indicator of temperature. However, in certain circumstances, electrical observations can provide strong constraints on mantle temperatures. In the southeastern United States (SEUS), magnetotelluric (MT) data require high resistivity values (>300 Ωm) to at least 200‐km depth. As dry mantle mineral conduction laws provide an upper bound on temperature for an observed resistivity value, the only interpretation is that lithospheric temperatures (<1330 °C) persist to 200 km. However, seismic tomography shows that velocities in this region are generally slightly slow with respect to references models; this observation has led to a view of relatively thin (<150 km), eroded thermal lithosphere beneath the SEUS. We show that MT and seismic (tomography, attenuation, receiver function) results are consistent with thick ( 200 km), coherent thermal lithosphere in this region. Reduced seismic velocities (relative to reference models) can be explained by considering the effect of finite grain size (anelasticity). Calculated velocity as a function of temperature is overall slower when including anelastic effects, even at reasonable grain sizes of 1 mm to 1 cm; this permits mantle temperatures that are colder than would typically be inferred. We argue for a geodynamic scenario in which the present thermal lithosphere in the SEUS formed in association with the Central Atlantic Magmatic Province and has subsequently survived intact for 200 Ma. Plain Language Summary: Seismic and magnetotelluric imaging techniques seem to give fundamentally different views of the mantle lithosphere beneath the southeastern United States (SEUS). Whereas seismic imaging has supported a picture of relatively thin, broken‐up lithosphere in this region, magnetotelluric imaging requires a thick, coherent lithospheric block in the SEUS. Here, by considering calculations of seismic observables including effects from finite grain size, we show that results from both geophysical data sets are consistent with this latter picture. Therefore, although previous studies have argued that the modern geodynamics of the SEUS is controlled by erosion and removal of lithosphere, our analysis supports a geodynamic scenario in which this region is underlain by a coherent lithospheric block that has survived intact for the last 200 million years. Key Points: Magnetotelluric and seismic imaging techniques appear to give contradictory views of the lithosphere in the southeastern United States Slow seismic velocities are consistent with high electrical resistivities in the mantle lithosphere when considering finite grain size Measured attenuation and lithospheric discontinuities are also consistent with high resistivities, which demand thick thermal lithosphere